2014
DOI: 10.1089/vbz.2014.1661
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Borrelia burgdorferi sensu stricto and Anaplasma phagocytophilum in Ixodes scapularis, Southwestern Virginia

Abstract: To determine the prevalence of Borrelia burgdorferi and Anaplasma phagocytophilum in a newly established population of Ixodes scapularis in the mountainous region of southwestern Virginia, questing adult ticks were collected and the identity and infection status of each tick was confirmed by PCR and sequencing. A total of 364 adult ticks were tested from three field sites. B. burgdorferi sensu stricto was identified in a total of 32/101 (32%) ticks from site A, 49/154 (32%) ticks from site B, and 36/101 (36%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
4
12
0
Order By: Relevance
“…Our study result of an overall seroprevalence of 33% to B. burgdorferi in horses also is identical to that of a recent study that identified a 33% prevalence of B. burgdorferi in ticks in southwest Virginia . Both studies also found prevalence rates to be similar in different geographic areas of the study region.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study result of an overall seroprevalence of 33% to B. burgdorferi in horses also is identical to that of a recent study that identified a 33% prevalence of B. burgdorferi in ticks in southwest Virginia . Both studies also found prevalence rates to be similar in different geographic areas of the study region.…”
Section: Discussionsupporting
confidence: 89%
“…With widespread travel of horses in the United States and the presence of vectors for B. burgdorferi in many areas of the country, spread of the disease out of the northeastern United States is likely . In fact, a recent study found that 33% of Ixodes scapularis ticks in southwest Virginia were infected with B. burgdorferi , thus confirming that the vector and organism are present in the area . According to the Center for Disease Control and Prevention (CDC), in 2013 there were 36,307 confirmed or probable cases of Lyme disease in humans in the United States with only 5 states reporting no cases .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 Similarly, increasing ranges for I. scapularis have been documented along the Hudson River Valley, Michigan, and Virginia. [32][33][34] Comparing the maps presented here with our previous surveillance summary from 2000 to 2007, anaplasmosis appears to be increasing in geographic range as well as in IR, consistent with changes in the range of its tick vector. 30 More cases were reported during 2008-2012 than during 2000-2007; and, analysis of human data in tandem with ecological data may elucidate changing risk of exposure to human populations.…”
Section: Methodssupporting
confidence: 77%
“…The greatest factors thought to affect spread were suitable climate and habitats that support white tailed deer and mice, and included waterways, river valleys and forests . In addition to studies performed that collected ticks nationwide, regional and/or statewide data are available in some cases . Part of the challenge in reviewing the literature is that there has been no standardized method or organization responsible for studying some of the important changes in Ixodes populations and B. burgdorferi presence or infection rates in dogs and horses and, as a result, data sets are more limited than is ideal.…”
Section: Seroprevalencementioning
confidence: 99%